Modéliser les dynamiques spatiales d’un tissu urbain dans la longue durée (en plan et en volume) - Bastien Lefebvre (In Situ)
In order to understand the spatial dynamics of the urban fabric implanted on the site of the antique amphitheatre of Tours, it is necessary to analyse the data gathered. In isolation, this data allows for certain significant items of information to be collated concerning for example the occupation of the site, but this information is of a partial nature. Spatial analysis can only be based on the confrontation of different levels of data. Modelling data using the HBDS method (Hypergraph Based Data Structure) emerges as an efficient method. The geographical deconstruction of the historical and archaeological data is first necessary. This preliminary stage allows not only to account for succeeding states but also to understand spatial dynamics.